Pedagogic Relations: A case study of English Language Learners in a Special Conversation Program - Welen Friade Sinaga; Harni Kartika Ningsih (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
Classroom interactions between a teacher and students are integral to the successful outcome of learning. However, research related to how knowledge is negotiated through teacher-student interaction is still rarely done, especially in Indonesia. This present article examines teacher-student interactions in a classroom setting during an English language learning organized by an informal institution in Laguboti, North Sumatera. Data were gathered through the observation of a recorded lesson demonstration under the Special Conversation program, involving a teacher and nine students. The video was transcribed and examined using the analytical framework of Pedagogic Registers (Rose, 2018), which focuses on pedagogic relations. The analysis revealed that the teacher conveyed authority throughout the learning process. Patterns of initial-response-feedback (I-R-F) were observed in the teaching, in which the teacher posed questions to engage passive students. In addition, students’ silence was identified as the most common challenge in such interactions. The study discovered that students’ silence urged the teacher to reflect on the challenges faced by the students during the learning process. Finally, it was found that the teacher evaluated learning outcomes by affirming and negating the students’ answers. A further study should be carried out to generate insights into more effective evaluation strategies for English language acquisition.